Emotional Maturity as a Predictor of Marital Adjustment among Individuals in Early Marriage in Bener Meriah Regency - Mariyani; Zirlia Anggraini; Dinda Khairunnisa; Budiman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2026)
The early stage of marriage is an important developmental phase, as individuals are required to adjust to new roles, responsibilities, and relational dynamics. Emotional maturity is considered a psychological factor that plays a significant role in successful self-adjustment during this period. This study aims to examine the relationship between emotional maturity and self-adjustment in the early stage of marriage. The proposed hypothesis is that there is a positive relationship between emotional maturity and self-adjustment. This research employed a quantitative approach with a correlational design. The participants were individuals in the early stage of marriage, selected using sampling techniques based on predetermined research criteria. Data were collected using emotional maturity and self-adjustment scales and analyzed using statistical correlation techniques. The results indicate a significant positive relationship between emotional maturity and self-adjustment. These findings emphasize the important role of emotional maturity in supporting successful self-adjustment during the early stage of marriage.